Nanoparticles in dentistry: A Review - NAMBIAR , Pallavi; MADHU , Priyanka Paul; RECH , Amit; MOHARIL, Shambhavi (International Arab Journal of Dentistry (IAJD), 2023)
Nanotechnology finds frequent application in everyday life, particularly in the field of medicine. Due to the capabilities of nanotechnology, examining and manipulating atoms, chemical bonds, and molecules between substances is a relatively straightforward task. When applied in the field of dentistry it is referred to as “nano dentistry”. Nanoparticles which are believed to possess superior efficacy, find significant usage in dentistry, primarily in the prevention and treatment of oral disorders, as well as the maintenance of good oral health and hygiene. Nanoparticles possess distinct characteristics such as their surface to volume ratio, antimicrobial activity, physical, mechanical and biological properties, as well as their particle size. This article provides an overview of the various nanoparticles utilized in dentistry and their respective contributions to the field.